Influence of the resonance in a gravity-gradient stabilized satellite - Moraes, R. Vilhena de; Silva, P. A. F. da [UNESP] (Springer Nature, 1989)
Using Hamiltonian formalism the translational-rotational motion of a satellite is studied near a resonance considering the orbital and rotational motions. A first order perturbation theory is derived by Hori's transformation in order to eliminate short and long periodic terms, preserving in the new Hamiltonian secular and resonant terms. This theory is again applied to study the resonant system whose analysis lead us to a system of equations equivalent to the equations of a simple pendulum which is integrable in terms of elliptical integrals. © 1990 Kluwer Academic Publishers.